2000
DOI: 10.1111/j.1574-6968.2000.tb08933.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene cloning, nucleotide sequence and biochemical properties of a cytoplasmic cyclomaltodextrinase (neopullulanase) fromAlicyclobacillus acidocaldarius, reclassification of a group of enzymes

Abstract: A gene encoding a cyclomaltodextrinase (neopullulanase) was cloned from the thermoacidophilic bacterium Alicyclobacillus acidocaldarius ATCC27009 and its nucleotide sequence was determined. The encoded CdaA protein lacked an N-terminal signal sequence and aligned well with a family of bacterial proteins described as maltogenic alpha-amylases, neopullulanases or cyclomaltodextrinases. Escherichia coli cells harboring the cloned cdaA gene produced a 66-kDa protein that degraded pullulan in a sodium dodecyl sulfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…According to literature, the amylase enzymes produced by microorganisms have optimum temperature ranges that vary from 45 to 115 ºC. 6,30 The results found in the present study were similar to those from studies by Bai et al, 26 and Matzke et al, 5 in the production of amylase by A. acidocaldarius.…”
Section: Determination Of Optimum Ph and Temperature Of Amylasesupporting
confidence: 82%
See 2 more Smart Citations
“…According to literature, the amylase enzymes produced by microorganisms have optimum temperature ranges that vary from 45 to 115 ºC. 6,30 The results found in the present study were similar to those from studies by Bai et al, 26 and Matzke et al, 5 in the production of amylase by A. acidocaldarius.…”
Section: Determination Of Optimum Ph and Temperature Of Amylasesupporting
confidence: 82%
“…29 With respect to species of Alicyclobacillus, the optimum pH range obtained in the present study was in accordance with the range reported in literature. The amylase enzyme produced by A. acidocaldarius ATCC 27009 had an optimum pH of 3.0, in a study by Matzke et al 5 In studies by Kumar et al, 25 of the production of amylase produced by A. acidocaldarius MTCC 8766, the optimum pH was 6.0. An acidic α-amylase produced by Alicyclobacillus sp.…”
Section: Determination Of Optimum Ph and Temperature Of Amylasementioning
confidence: 99%
See 1 more Smart Citation
“…docaldarius (29,56). We note that the intracellular location of AaManA and its preference for longer substrates requires a special manno-oligosaccharide uptake system, because such substrates are too large to passively cross the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Pullulan hydrolase type I (neopullulanase) and type II (isopullulanase) are only able to cleave α -1,4 glucosidic linkages in pullulan, releasing panose and isopanose, and are highly active on cyclodextrins [3234]. The enzymes that degrade cyclodextrins faster than starch are sometimes designated cyclodextrinases (EC 3.2.1.54, cyclomaltodextrinase) [3, 34]. Interestingly, cyclomaltodextrinases are intracellular enzymes whereas most enzymes involved in starch conversion are extracellular [35].…”
Section: Starch-debranching Enzymesmentioning
confidence: 99%